Stages of Development of the Science of Linguistics and Culture - Yusupova Gulnora (Scholars Digest Publishing, 2023)
Todays, economic, social, cultural and scientific relations between peoples and nations are getting stronger. Therefore, communication reflects the interrelationship of language with culture and language. From the beginning of the 20th century, scientists who study language and culture realized that these areas can be the basis of a new science. This field was named by them as linguistic and cultural studies. That is, the foundation of a new science of modern linguistics, which includes language and culture, has been laid. At the end of the 20th century, three problems were applied in this field: language, culture and human personality. The main goal was to activate knowledge about language and culture.
Keywords: linguistics, Linguoculturology, components, culture, intercultural communication, linguoculture, speech, language, lexicography